Effects of gamma ray and electron beam irradiation levels in spray-dried blood meal on nursery pig performance - Woodworth, J.C.; Webster, M.J.; James, B.J.; Real, D.E.; DeRouchey, Joel M.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three hundred weanling pigs (initially 23.7 lbs and 17 ± 6 d of age) were used in a 19-d growth assay to determine the effects of increasing levels (2.5, 5.0, and 10.0, and 20.0 kGy) of gamma ray and electron beam irradiation of spray-dried blood meal on growth performance. Irradiation of blood meal resulted in decreased concentrations of aerobic bacteria, E. coli, mold, and yeast in spray-dried blood meal. The inclusion of irradiated spray-dried blood meal tended to improve F/G from d 0 to 7 and for the overall trial (d 0 to 14), but had no effects on ADG or ADFI. Comparison of the two types of irradiation and dosage level showed no differences in growth performance. In this experiment, the inclusion of spray-dried blood meal did not improve growth performance over that obtained with the control diet.
Keywords: Swine; Nursery pig; Blood meal; Irradiation